How the Volume-based Waste Fee Policy Increased Household Recycling Rates in the Republic of Korea (1995-2009) - Kim, Dong Young (Global Delivery Initiative, 2019)
With approximately 60 percent recycling and composting rates, South Korea has been heralded as one of the highest recyclers of municipal solid waste among OECD countries. The Volume-based Waste Fee (VWF) policy, which South Korea introduced in 1995 as a developing country, has helped increase household recycling rates. As a result, the increased amount of recycled and composted waste has diverted waste from landfills and incinerators and relieved the burden of municipal governments to find or site new waste infrastructures in Korea. To reap the benefits of a VWF policy, all key stakeholders play an important role in the implementation loop: citizens who separate wastes and purchase designated plastic bags; local government who collect recyclable materials; and recycling industries who reprocess those materials. The delivery challenge is to make citizens see waste separation as convenient and to believe their behaviors will make real and positive impacts on environment. Stakeholder engagement and coordination become very important in overcoming such challenges, so it is important that governments solicit and incorporate citizens’ ideas on more convenient waste separation schemes into its policy. The story of the VWF policy in Korea is about a story of trial and error, and navigating through a complex arrangement of factors in the waste management system in order to connect the dots in the implementation loop through the gradual engagement of all stakeholders. With the increased level of awareness of the serious waste problem in Korea, the government built up administrative capacity step-by-step with legal provisions, creating necessary organizations with human resources, and providing budget line items as appropriate. However, the road to success did not start perfectly. Pilot tests were monitored, evaluated, and gradually improved upon. The key to success was how to navigate through the complex arrangement of factors in the waste management system. Ultimately, communication was the key to getting to know the interests of the stakeholders and ascertain their concerns about the VWF policy. Participation of non-governmental actors was critical to success as it allowed their opinions to be incorporated in policy adjustments.